2012
DOI: 10.3851/imp2452
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Second-Line Lopinavir/ Ritonavir Monotherapy versus Tenofovir/Lamivudine/ Lopinavir/Ritonavir in Patients Failing Nnrti Regimens: The HIV Star Study

Abstract: The publisher would like to report an omission from a recently published article [1]. The title of Figure 3 should contain '(A)' and '(B)', and the correct title and corresponding figure are shown. The publisher apologizes for this omission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 1 publication
1
32
0
Order By: Relevance
“…A recent Thai study randomized subjects failing first-line ART to either LPV/r monotherapy or LPV/r, FTC and TDF, and was conducted simultaneously with ACTG A5230 [25]. They observed that the proportion of subjects with viremia at levels 50–400 after 48 weeks was significantly higher in the monotherapy arm (14% versus 3%), leading them to conclude that 3-drug second-line regimens were superior.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Thai study randomized subjects failing first-line ART to either LPV/r monotherapy or LPV/r, FTC and TDF, and was conducted simultaneously with ACTG A5230 [25]. They observed that the proportion of subjects with viremia at levels 50–400 after 48 weeks was significantly higher in the monotherapy arm (14% versus 3%), leading them to conclude that 3-drug second-line regimens were superior.…”
Section: Discussionmentioning
confidence: 99%
“…In PI-naive adults failing an non-NRTI (NNRTI)-based first line regimen without TDF, 83% achieved virologic suppression after switching to TDF/lamivudine/ lopinavir/r. 43 In a study of heavily pretreated HIV-infected children, of whom 72% had ≥3 TAM with M41L mutation, adding TDF to the optimized background regimen (OBR) resulted in >1.0 log 10 copies/mL reduction of median HIV viral load among 15 of 18 children, with virologic suppression in 6 of 18 children by 48 weeks. 44 In a study of HIV-infected adolescents with pre-existing resistance mutations (49% of cases had ≥3 TAMs with either M41L or L210W) randomized to receive TDF or placebo with OBR, 41% of subjects overall achieved virologic suppression, but there was no difference between the TDF and placebo arms.…”
Section: Tdf As Part Of Second-line or Third-line Arv Regimensmentioning
confidence: 99%
“…[26][27][28] The other small 48-week comparative trial in Thailand showed that protease-inhibitor monotherapy was inferior to protease-inhibitor therapy plus NRTIs on the basis of lower rates of viral-load suppression to a level under 50 copies per milliliter (with only a trend toward lower rates of suppression to a level under 400 copies per milliliter and little protease-inhibitor resistance). 29 Since outcomes with protease-inhibitor monotherapy are better when treatment is initiated after viral-load suppression, 6,30,31 we used an induction approach with raltegravir. A longer induction period or a strategy including regular viral-load monitoring with immediate NRTI reintensification after viral-load rebound might have produced better outcomes, but such a regimen would be challenging to implement and would diminish the potential practical and cost advantages of protease-inhibitor monotherapy in resourcelimited settings.…”
Section: Discussionmentioning
confidence: 99%